Useful woody species and its environmental availability: the case of artisanal fishermen in Itaúnas, Brazil - Lopes, Lucas Costa Monteiro; Crepaldi, Maria Otávia Silva; Lobão, Adriana Quintella (Acta Scientiarum. Biological Sciences, 2017)
Ethnobotanical studies involve research with human societies and their different interaction with plants, and the quantitative approaches from thes estudies are important to select conservation priority of species in natural environment. This research aims to quantify use-values for woody plants mentioned by fishers in Itaúnas, state of Espírito Santo, and evaluate the relationship between use-values and species availability (absolute density and frequency, and importance value) in two distinct resting vegetation formations. It also proposes to identify priority species for conservation. It was selected 30 species cited in individual semi-structured interviews with key-informant in fishers’ community and who were also on list of structural survey of two vegetation phytophysiognomies in the restinga regions. The data used was collected in previously published work. It was performed a correlation analysis between use-values and structural parameters of the mentioned woody species. Protium heptaphyllum, P. icicariba and Byrsonima sericea present the highest use-values. It was not observed relation between use-value and species availability in each vegetation formation. It was classified two and eight species as priority for conservation on shrubby and forest formations, respectively.